A fine aggregate concrete with anti-dispersion properties for synchronous grouting in TBM tunnels and its preparation method
By using anti-dispersion fine aggregate concrete, the problems of incomplete backfilling and segment disturbance in TBM tunnel walls were solved, achieving high-performance backfilling and improving the tunnel's impermeability and construction safety.
Patent Information
- Application Number
- CN202310784589.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2043-06-29
AI Technical Summary
In the existing TBM tunnel wall backfilling process, the cement slurry cannot be evenly diffused, resulting in incomplete filling. Furthermore, the crushed stone filling and grouting processes disturb the tunnel segments, affecting the overall impermeability and construction safety of the tunnel.
Anti-dispersion fine aggregate concrete is adopted, which combines silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash, ultrafine silica powder and other raw materials, and adds admixtures such as nano silica and carbon fiber to form high-performance concrete, which can be poured in one go and improve density and stability.
It improved the density of the backfill behind the tunnel wall, reduced the impact on the tunnel lining segments, enhanced the tunnel's impermeability and mechanical properties, and ensured construction safety and long-term durability.
Smart Images

Figure GDA0005404414870000131 
Figure GDA0005404414870000141
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of backfill materials for urban subway TBM tunnel walls, and mainly relates to an anti-dispersion fine stone concrete for synchronous grouting of TBM tunnels and its preparation method. This material is used for backfilling of TBM tunnel walls. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] TBM (Transporter-Built) construction has gradually become the mainstream method for underground tunnel construction. As the TBM advances, its cutterhead diameter is typically slightly larger than the outer diameter of the tunnel segments, creating a gap of approximately 15cm between the segment wall and the ground. To improve the overall impermeability of the tunnel and avoid ground deformation and stress concentration issues caused by this gap, backfilling is necessary. TBM segment backfilling typically involves two steps: crushed stone shoveling and cement grouting. First, as much crushed stone as possible is shoveled before and after the third ring of tunnel segments, ensuring complete filling of the backfill gap. Due to gravity, approximately 180° and 120° of crushed stone will slide down from the bottom of the first two rings of tunnel segments, providing support. Simultaneously with crushed stone shoveling, grouting is performed at the 15th ring of tunnel segments and even further from the tail shield. However, this backfilling method has a series of drawbacks: for example, cement slurry often cannot be evenly spread between the crushed stones, resulting in incomplete backfilling; the two processes of crushed stone blowing and cement slurry injection cause two disturbances to the segments, leading to problems such as segment displacement, misalignment, and even damage.
[0004] To address the aforementioned issues, existing projects have modified the TBM tail grout stop plate, replacing the traditional single-blade type with an open double-blade type. One blade overlaps the tunnel segment, and the other overlaps the ground layer, improving the grout-stopping effect of the steel plate. Then, simultaneous grouting is performed on the TBM. To minimize grout leakage and achieve simultaneous grouting of the TBM, a one-time injection of fine aggregate concrete can replace the traditional two-stage backfilling process of crushed stone filling and backfilling grouting. This improves the density of the backfill and reduces the impact on the tunnel segment structure. Therefore, there is an urgent need to develop a high-performance concrete material with good stability, enabling dense backfilling and stable support through a one-time injection of this concrete. Summary of the Invention
[0005] To address the aforementioned problems and further improve the water dispersion resistance and performance of backfill materials, this invention proposes a high-performance underwater non-dispersible concrete for tunnel lining backfill and its preparation method. This material possesses excellent water dispersion resistance, short setting time, and superior mechanical properties, which is beneficial for improving the underwater retention rate of the material, the overall mechanical properties and impermeability of the tunnel, and has significant practical implications for controlling segment displacement, improving backfill effect, and ensuring construction safety.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides an anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels, characterized in that it is composed of the following raw materials in parts by weight: 120 parts silicate cement, 100-180 parts fly ash, 60-100 parts calcined coal gangue powder, 70-150 parts construction waste powder, 40-80 parts biomass ash, 30-50 parts ultrafine silica fume, 400-600 parts recycled fine aggregate from construction waste, and 200-3 parts recycled coarse aggregate from coal gangue. 00 parts, fine gravel 300-500 parts, water 240-320 parts, nano silica 6-10 parts, carbon fiber 2-5 parts, copper-plated steel fiber 5-8 parts, polyacrylamide 1-3 parts, modified cellulose ether 2-4 parts, xanthan gum 1-2 parts, sodium carboxymethyl cellulose 0.5-1 part, acrylate copolymer 0.5-1 part, starch 1-2 parts, triethanolamine 0.2-0.3 parts, polycarboxylate superplasticizer 1.5-2.5 parts, cement expansion agent 3-5 parts.
[0008] This invention modifies the concrete of the backfill layer behind the TBM tunnel wall by adding certain admixtures. On the one hand, the concrete can adapt to the water-rich environment behind the tunnel segment wall, remain stable when uniformly injected into water, and is not diluted or dispersed by water. After being injected into the tunnel segment wall through the lifting hole, it can achieve self-leveling and self-compacting. On the other hand, the toughness of the concrete is significantly enhanced compared to conventional materials, which can more effectively resist the repeated cyclic vibration loads of trains. At the same time, its volume stability and impermeability are good, which can meet the working performance and long-term durability requirements of TBM tunnels.
[0009] A second aspect of the present invention provides a method for preparing the above-mentioned anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels, comprising the following steps:
[0010] Ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed evenly to obtain a cementitious powder.
[0011] The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue, and fine stones are mixed evenly to obtain concrete mix.
[0012] Nano-silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed evenly to obtain a high-performance concrete admixture.
[0013] The concrete mix, high-performance admixture, and water are mixed evenly to obtain the final product.
[0014] A third aspect of the invention provides the application of the above-described concrete in the preparation of backfill material for TBM tunnel walls.
[0015] Beneficial effects of the present invention
[0016] (1) This invention utilizes resources such as multi-source solid waste and urban construction waste with high added value, and prepares them into anti-dispersion fine stone concrete for backfilling of TBM tunnel segment walls.
[0017] (2) This invention addresses the problem of easy dispersion and dilution of backfill materials caused by the water-rich environment behind the tunnel lining segments. By controlling the dosage of each raw material component and admixture in the concrete, the water resistance and toughness of the concrete are improved. Furthermore, by injecting this concrete material in a single pour, replacing the traditional two-stage backfilling process of crushed stone filling and backfill grouting, the density of the backfill is improved and the impact on the tunnel lining segment structure is reduced. This invention is beneficial for improving the overall impermeability, mechanical properties, and durability of TBM tunnels, ensuring the long-term safety of tunnel construction and operation.
[0018] (3) The operation method of this application is simple, has certain economic advantages compared with traditional materials, and is highly targeted, and can be promoted in similar TBM tunnel synchronous grouting projects. Detailed Implementation
[0019] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0020] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels is composed of the following raw materials in parts by weight: 120 parts silicate cement, 100-180 parts fly ash, 60-100 parts calcined coal gangue powder, 70-150 parts construction waste powder, 40-80 parts biomass ash, 30-50 parts ultrafine silica fume, 400-600 parts recycled fine aggregate from construction waste, 200-300 parts recycled coarse aggregate from coal gangue, and 300 parts fine aggregate. -500 parts, water 240-320 parts, nano silica 6-10 parts, carbon fiber 2-5 parts, copper-plated steel fiber 5-8 parts, polyacrylamide 1-3 parts, modified cellulose ether 2-4 parts, xanthan gum 1-2 parts, sodium carboxymethyl cellulose 0.5-1 part, acrylate copolymer 0.5-1 part, starch 1-2 parts, triethanolamine 0.2-0.3 parts, polycarboxylate superplasticizer 1.5-2.5 parts, cement expansion agent 3-5 parts.
[0021] This invention uses ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash, and ultrafine silica powder to form a cementitious powder. It uses recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue, and fine stones as aggregates. At the same time, it uses nano-silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer, and cement expansion agent as high-performance admixtures for concrete. The raw materials are formed in the environment behind the tunnel lining wall to obtain a dense, mechanically strong, and anti-dispersion fine stone concrete.
[0022] Compared with ordinary silicate cement, the cementitious material of this invention has the advantages of high stone formation rate, good mechanical properties, and good durability, while reducing cement content and providing a feasible path for solid waste disposal. Construction waste powder can act as a filler, improving the compressive strength and stone formation rate of the material, while reducing cement usage and facilitating the efficient and high-value-added recycling of construction waste. Biomass ash contains a large amount of alkaline oxides, which can provide alkalinity to the material system, thereby activating mineral admixtures such as fly ash and coal gangue. At the same time, the calcium and silicon oxides contained in biomass ash can also supplement the system with calcium and silicon. The average particle size of ultrafine silica powder is very small, thus increasing the cohesiveness of the material and improving its bonding performance, compressive strength, and durability.
[0023] Compared to traditional aggregates, the three types of aggregates in this invention are all obtained from processed solid waste, thus offering a primary advantage in environmental protection. Construction waste and coal gangue are both solid wastes with massive stockpiles and difficult treatment processes; using them as aggregates without compromising performance is an excellent way to utilize them, thereby alleviating the pressure of solid waste treatment. Furthermore, both the fine aggregate from construction waste and the recycled coarse aggregate from coal gangue contain soluble components, enabling them to combine with cementitious materials and form a more stable hydration product structure on the surface. The use of recycled aggregates has minimal impact on compressive strength, therefore they can be used in materials.
[0024] In some embodiments, the fly ash is grade II fly ash with an average particle size of 20.45–25 μm.
[0025] In some embodiments, the calcined coal gangue is obtained by crushing and grinding raw coal gangue and then calcining it at 500-800°C for 2-3 hours, with an average particle size of 25.38-30 μm, preferably at 600-700°C.
[0026] In some embodiments, the construction waste powder is a powder obtained by crushing and grinding construction waste, with an average particle size of 39.73 to 42 μm.
[0027] In some embodiments, the average particle size of the biomass ash is 33.50–35 μm.
[0028] In some embodiments, the average particle size of the ultrafine silica powder is 0.1-0.15 μm.
[0029] In some embodiments, the recycled fine aggregate from construction waste is microparticles obtained by crushing and screening construction waste, with a continuous gradation of particle size less than 5 mm.
[0030] In some embodiments, the recycled coarse aggregate from coal gangue is aggregate obtained after coal gangue has been crushed, screened, and impurities removed, with a particle size range of 4.75-16 mm.
[0031] In some embodiments, the particle size of the fine stones ranges from 5 mm to 15 mm.
[0032] In some embodiments, the average particle size of the nano-silica is 20–22 nm;
[0033] In some embodiments, the carbon fiber has a length of 6-8 mm and a thickness of 6-7 μm;
[0034] In some embodiments, the copper-plated steel fiber has a length of 13-15 mm and a thickness of 0.2 mm;
[0035] Alternatively, the polyacrylamide is anionic and has a molecular weight of not less than 5 million;
[0036] In some embodiments, the modified cellulose ether is obtained by modifying the cellulose ether with aldehydes, and the viscosity is not less than 100,000.
[0037] In some embodiments, the polycarboxylate superplasticizer has a solid content ≥98% and a water reduction rate of 36.2%.
[0038] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are explanations of the present invention and not limitations thereof.
[0039] The anti-dispersion fine aggregate concrete for synchronous grouting of TBM tunnels prepared using the formula of the present invention is used as an example. Comparative examples are also set up for comparison. A total of 5 examples and 10 comparative examples are set up. The content of the components in all examples and comparative examples is expressed in parts by mass.
[0040] The specific specifications of each raw material are as described above. The calcined coal gangue is obtained by calcining raw coal gangue at 650°C for 2 hours after crushing and grinding, with an average particle size of 25.38 μm.
[0041] The modified cellulose ether was hydroxypropyl methylcellulose, purchased from Shandong Hongquan Chemical Technology Co., Ltd.
[0042] The cement expansion agent was purchased from Nanjing Steibo Trading Co., Ltd.
[0043] Example 1
[0044] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels comprises the following components by weight: 120 parts ordinary silicate cement, 100 parts fly ash, 60 parts calcined coal gangue powder, 70 parts construction waste powder, 40 parts biomass ash, 30 parts ultrafine silica powder, 400 parts recycled fine aggregate from construction waste, 200 parts recycled coarse aggregate from coal gangue, 300 parts fine gravel, 240 parts water, 6 parts nano-silica, 2 parts carbon fiber, 5 parts copper-plated steel fiber, 1 part polyacrylamide, 2 parts modified cellulose ether, 1 part xanthan gum, 0.5 parts sodium carboxymethyl cellulose, 0.5 parts acrylate copolymer, 1 part starch, 0.2 parts triethanolamine, 1.5 parts polycarboxylate superplasticizer, and 3 parts cement expansion agent.
[0045] Its preparation method is as follows:
[0046] Weigh each raw material according to the above-mentioned weight proportions;
[0047] (1) The ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed in proportion to obtain a cementitious powder;
[0048] (2) The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue and fine stones are mixed in proportion to obtain concrete mix;
[0049] (3) Nano silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed in proportion to obtain a high-performance concrete admixture.
[0050] (4) Mix the concrete mix, high-performance admixture and water in proportion to obtain TBM tunnel synchronous grouting anti-dispersion fine stone concrete.
[0051] Example 2
[0052] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels comprises the following components by weight: 120 parts ordinary silicate cement, 120 parts fly ash, 70 parts calcined coal gangue powder, 90 parts construction waste powder, 50 parts biomass ash, 35 parts ultrafine silica powder, 450 parts recycled fine aggregate from construction waste, 225 parts recycled coarse aggregate from coal gangue, 350 parts fine gravel, 260 parts water, 7 parts nano-silica, 3 parts carbon fiber, 6 parts copper-plated steel fiber, 1.5 parts polyacrylamide, 2.5 parts modified cellulose ether, 1.3 parts xanthan gum, 0.6 parts sodium carboxymethyl cellulose, 0.6 parts acrylate copolymer, 1.3 parts starch, 0.23 parts triethanolamine, 1.8 parts polycarboxylate superplasticizer, and 3.5 parts cement expansion agent.
[0053] Its preparation method is as follows:
[0054] Weigh each raw material according to the above-mentioned weight proportions;
[0055] (1) The ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed in proportion to obtain a cementitious powder;
[0056] (2) The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue and fine stones are mixed in proportion to obtain concrete mix;
[0057] (3) Nano silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed in proportion to obtain a high-performance concrete admixture.
[0058] (4) Mix the concrete mix, high-performance admixture and water in proportion to obtain TBM tunnel synchronous grouting anti-dispersion fine stone concrete.
[0059] Example 3
[0060] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels comprises the following components by weight: 120 parts ordinary silicate cement, 140 parts fly ash, 80 parts calcined coal gangue powder, 110 parts construction waste powder, 60 parts biomass ash, 40 parts ultrafine silica powder, 500 parts recycled fine aggregate from construction waste, 250 parts recycled coarse aggregate from coal gangue, 400 parts fine gravel, 280 parts water, 8 parts nano-silica, 3.5 parts carbon fiber, 6.5 parts copper-plated steel fiber, 2 parts polyacrylamide, 3 parts modified cellulose ether, 1.5 parts xanthan gum, 0.75 parts sodium carboxymethyl cellulose, 0.75 parts acrylate copolymer, 1.5 parts starch, 0.25 parts triethanolamine, 2 parts polycarboxylate superplasticizer, and 4 parts cement expansion agent.
[0061] Its preparation method is as follows:
[0062] Weigh each raw material according to the above-mentioned weight proportions;
[0063] (1) The ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed in proportion to obtain a cementitious powder;
[0064] (2) The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue and fine stones are mixed in proportion to obtain concrete mix;
[0065] (3) Nano silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed in proportion to obtain a high-performance concrete admixture.
[0066] (4) Mix the concrete mix, high-performance admixture and water in proportion to obtain TBM tunnel synchronous grouting anti-dispersion fine stone concrete.
[0067] Example 4
[0068] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels comprises the following components by weight: 120 parts ordinary silicate cement, 160 parts fly ash, 90 parts calcined coal gangue powder, 130 parts construction waste powder, 70 parts biomass ash, 45 parts ultrafine silica fume, 550 parts recycled fine aggregate from construction waste, 275 parts recycled coarse aggregate from coal gangue, 450 parts fine gravel, 300 parts water, 9 parts nano-silica, 4 parts carbon fiber, 7 parts copper-plated steel fiber, 2.5 parts polyacrylamide, 3.5 parts modified cellulose ether, 1.8 parts xanthan gum, 0.9 parts sodium carboxymethyl cellulose, 0.9 parts acrylate copolymer, 1.8 parts starch, 0.28 parts triethanolamine, 2.3 parts polycarboxylate superplasticizer, and 4.5 parts cement expansion agent.
[0069] Its preparation method is as follows:
[0070] Weigh each raw material according to the above-mentioned weight proportions;
[0071] (1) The ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed in proportion to obtain a cementitious powder;
[0072] (2) The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue and fine stones are mixed in proportion to obtain concrete mix;
[0073] (3) Nano silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed in proportion to obtain a high-performance concrete admixture.
[0074] (4) Mix the concrete mix, high-performance admixture and water in proportion to obtain TBM tunnel synchronous grouting anti-dispersion fine stone concrete.
[0075] Example 5
[0076] An anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels comprises the following components by weight: 120 parts ordinary silicate cement, 180 parts fly ash, 100 parts calcined coal gangue powder, 150 parts construction waste powder, 80 parts biomass ash, 50 parts ultrafine silica powder, 600 parts recycled fine aggregate from construction waste, 300 parts recycled coarse aggregate from coal gangue, 500 parts fine gravel, 320 parts water, 10 parts nano-silica, 5 parts carbon fiber, 8 parts copper-plated steel fiber, 3 parts polyacrylamide, 4 parts modified cellulose ether, 2 parts xanthan gum, 1 part sodium carboxymethyl cellulose, 1 part acrylate copolymer, 2 parts starch, 0.3 parts triethanolamine, 2.5 parts polycarboxylate superplasticizer, and 5 parts cement expansion agent.
[0077] Its preparation method is as follows:
[0078] Weigh each raw material according to the above-mentioned weight proportions;
[0079] (1) The ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed in proportion to obtain a cementitious powder;
[0080] (2) The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue and fine stones are mixed in proportion to obtain concrete mix;
[0081] (3) Nano silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed in proportion to obtain a high-performance concrete admixture.
[0082] (4) Mix the concrete mix, high-performance admixture and water in proportion to obtain TBM tunnel synchronous grouting anti-dispersion fine stone concrete.
[0083] Comparative Example 1
[0084] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include nano-SiO2, and nano-SiO2 is not added during sample preparation.
[0085] Comparative Example 2
[0086] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include copper-plated steel fibers, and no copper-plated steel fibers are added during sample preparation.
[0087] Comparative Example 3
[0088] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include modified cellulose ether, and no modified cellulose ether is added during sample preparation.
[0089] Comparative Example 4
[0090] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include triethanolamine, and triethanolamine is not added during sample preparation.
[0091] Comparative Example 5
[0092] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include polycarboxylate superplasticizer, and no polycarboxylate superplasticizer is added during sample preparation.
[0093] Comparative Example 6
[0094] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include cement expansion agent, and no cement expansion agent is added during sample preparation.
[0095] Comparative Example 7
[0096] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include nano-silica, carbon fiber, or copper-plated steel fiber, and nano-silica, carbon fiber, or copper-plated steel fiber are not added during sample preparation.
[0097] Comparative Example 8
[0098] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include polyacrylamide and modified cellulose ether, and no polyacrylamide and modified cellulose ether are added during sample preparation.
[0099] Comparative Example 9
[0100] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer and starch. Polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer and starch are not added during sample preparation.
[0101] Comparative Example 10
[0102] The only difference between this comparative example and Example 3 is that the raw material components of the anti-dispersion fine aggregate concrete do not include triethanolamine, polycarboxylate superplasticizer and cement expansion agent, and triethanolamine, polycarboxylate superplasticizer and cement expansion agent are not added during sample preparation.
[0103] Example effect verification:
[0104] After preparing and curing the concrete aggregates in Examples 1-5 and Comparative Examples 1-10 to the specified age, flowability, drying shrinkage, compressive strength, flexural strength, and impermeability tests were conducted according to the operating procedures specified in DL / T5117-2021 "Test Procedure for Underwater Non-Dispersible Concrete". The mass of the non-dispersible fine aggregate concrete before and after being washed by 0.5 m / s water for 1 hour was tested to obtain the water retention rate. Specimens were formed in water and on land, and the 28-day water-to-land strength ratio was calculated. The specific test results are shown in the table below.
[0105] Table 1. Performance test results of concrete in the examples and comparative examples.
[0106]
[0107]
[0108] As shown in Table 1 above, compared with Comparative Examples 1-10, the anti-dispersion fine aggregate concrete prepared using the raw material formula and preparation method of the present invention for synchronous grouting of TBM tunnels has better overall performance in Examples 1-5. Among them, the slump of Example 3 is 138 mm, the shrinkage rate is 0.03%, the 24-hour compressive strength is 1.6 MPa, the 28-day compressive strength is 15.84 MPa, the flexural-compression ratio is 0.27, the dynamic water retention rate is 95.8%, and the water-land strength ratio is 95.2%, which meets the requirements of synchronous grouting projects.
[0109] Compared with Comparative Example 1, Example 3 incorporates nano-SiO2. Nano-SiO2 can fill the network structure formed by the high-performance admixture, thereby enhancing the viscosity and interaction of each component as a whole, improving the cohesiveness between materials inside the concrete, reducing defects in the internal structure of the concrete, making the concrete denser, improving its cohesiveness, workability, compressive strength, flexural-to-compression ratio, and resistance to erosion.
[0110] Compared with Comparative Example 2, Example 3 incorporates copper-plated steel fibers, which can reinforce the transition zone of the dispersed fine aggregate concrete interface at the millimeter scale, thereby increasing the concrete's flexural-compression ratio.
[0111] Compared with Comparative Example 3, Example 3 added modified cellulose ether. Modified cellulose ether can dissolve and be uniformly dispersed in the suspension, increasing the viscosity of the system, preventing the rapid deposition of concrete mix particles, improving the water retention properties of concrete, and significantly improving the dynamic water retention rate and water-to-land strength ratio of concrete.
[0112] Compared with Comparative Example 4, Triethanolamine was added in Example 3. On the one hand, the emulsifying effect of Triethanolamine caused it to be adsorbed on the surface of the cementitious powder particles, which hindered the aggregation of the cementitious powder particles and produced a suspension stabilization effect. On the other hand, the dissolution of Triethanolamine in water reduced the surface tension of the slurry, which made the cementitious powder more fully contacted with water, accelerated the polymerization reaction of the cementitious powder, and improved the early strength of the concrete.
[0113] Compared with Comparative Example 5, Example 3 added a polycarboxylate superplasticizer. On the one hand, the superplasticizer can be adsorbed on the surface of the cementitious powder particles to exert electrostatic repulsion and lubrication. On the other hand, the long-chain structure of the polycarboxylate superplasticizer can exert steric hindrance, alleviate the thickening effect of the modified cellulose ether on the system, improve the workability of concrete, improve the injectability of concrete, improve the compressive strength, and improve the impermeability.
[0114] Compared with Comparative Example 6, Example 3 added a cement expansion agent, which effectively reduced the surface tension of the pore solution and significantly reduced the shrinkage rate of the concrete.
[0115] Compared with Comparative Example 7, Example 3 incorporates nano-silica, carbon fiber, and copper-plated steel fiber. Nano-silica fills the network structure formed by the high-performance admixture, while carbon fiber and copper-plated steel fiber reinforce the transition zone of the concrete interface at the millimeter scale. Simultaneously, the high molecular weight and large specific surface area comb-like structure of the high-performance admixture itself help the cementitious powder become a whole, giving the concrete a more stable structure. Nano-silica increases the viscosity of each component as a whole. The interaction of multiple components reduces internal structural defects in the concrete, making it more compact and significantly enhancing the flexural-compression ratio.
[0116] Compared with Comparative Example 8, Example 3 added polyacrylamide and modified cellulose ether. Polyacrylamide has good flocculation properties and can reduce the frictional resistance between suspensions. Modified cellulose ether can dissolve and disperse evenly in the suspension, increase the viscosity of the system, prevent the concrete mix particles from settling too quickly, improve the water retention properties of concrete, and significantly improve the dynamic water retention rate and water-to-land strength ratio of concrete.
[0117] Compared with Comparative Example 9, Example 3 added polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer and starch. The viscosity of the suspension system increased significantly, the water retention of concrete was enhanced, and the dynamic water retention rate and water-land strength ratio were significantly improved.
[0118] Compared with Comparative Example 10, Example 3 added triethanolamine, polycarboxylate superplasticizer and cement expansion agent, which enhanced the water retention, fluidity and cohesiveness of concrete, reduced shrinkage, significantly improved early strength and later strength, and increased the flexural-compression ratio.
[0119] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A type of anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels, characterized in that, It is composed of the following raw materials in parts by weight: 120 parts silicate cement, 100-180 parts fly ash, 60-100 parts calcined coal gangue powder, 70-150 parts construction waste powder, 40-80 parts biomass ash, 30-50 parts ultrafine silica powder, 400-600 parts recycled fine aggregate from construction waste, 200-300 parts recycled coarse aggregate from coal gangue, 300-500 parts fine gravel, 240-320 parts water, 6-10 parts nano silica, 2-5 parts carbon fiber, 5-8 parts copper-plated steel fiber, 1-3 parts polyacrylamide, 2-4 parts modified cellulose ether, 1-2 parts xanthan gum, 0.5-1 part sodium carboxymethyl cellulose, 0.5-1 part acrylate copolymer, 1-2 parts starch, 0.2-0.3 parts triethanolamine, 1.5-2.5 parts polycarboxylate superplasticizer, and 3-5 parts cement expansion agent. The method for preparing anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels includes the following steps: Ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed evenly to obtain a cementitious powder. The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue, and fine stones are mixed evenly to obtain concrete mix. Nano-silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed evenly to obtain a high-performance concrete admixture. The concrete mix, high-performance admixture, and water are mixed evenly to obtain the final product.
2. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The fly ash has a fineness of grade II fly ash with an average particle size of 20.45~25μm.
3. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The calcined coal gangue is obtained by crushing and grinding raw coal gangue and then calcining it at 650~700℃ for 2~3 hours, with an average particle size of 25.38~30μm.
4. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The construction waste powder is a powder obtained by crushing and grinding construction waste, with an average particle size of 39.73~42μm.
5. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The average particle size of the biomass ash is 33.50~35μm.
6. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The average particle size of the ultrafine silica powder is 0.1-0.15 μm.
7. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The recycled fine aggregate from construction waste is a continuous gradation of particles obtained from construction waste after crushing and screening, with a particle size of less than 5 mm. Alternatively, the recycled coarse aggregate from coal gangue is aggregate obtained after coal gangue has been crushed, screened, and impurities removed, with a particle size range of 4.75-16mm. Alternatively, the particle size of the fine stones may range from 5mm to 15mm.
8. The anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels as described in claim 1, characterized in that, The carbon fiber has a length of 6-8 mm and a thickness of 6-7 μm; Alternatively, the copper-plated steel fiber has a length of 13-15 mm and a thickness of 0.2 mm; Alternatively, the polyacrylamide is anionic and has a molecular weight of not less than 5 million; Alternatively, the modified cellulose ether is obtained by modifying cellulose ether with aldehydes, and the viscosity is not less than 100,000. Alternatively, the polycarboxylate superplasticizer has a solid content of ≥98% and a water reduction rate of 36.2%.
9. A method for preparing anti-dispersion fine aggregate concrete for synchronous grouting in TBM tunnels according to any one of claims 1-8, comprising the following steps: Ordinary silicate cement, fly ash, calcined coal gangue powder, construction waste powder, biomass ash and ultrafine silica powder are mixed evenly to obtain a cementitious powder. The cementitious powder, recycled fine aggregate from construction waste, recycled coarse aggregate from coal gangue, and fine stones are mixed evenly to obtain concrete mix. Nano-silica, carbon fiber, copper-plated steel fiber, polyacrylamide, modified cellulose ether, xanthan gum, sodium carboxymethyl cellulose, acrylate copolymer, starch, triethanolamine, polycarboxylate superplasticizer and cement expansion agent are mixed evenly to obtain a high-performance concrete admixture. The concrete mix, high-performance admixture, and water are mixed evenly to obtain the final product.
10. The use of the concrete according to any one of claims 1-8 in the preparation of backfill material for TBM tunnel walls.
Citation Information
Patent Citations
Underwater non-dispersible ultra-high performance concrete and preparation method thereof
CN114436582A
High-performance underwater non-dispersible concrete for back filling of tunnel lining wall and preparation method of high-performance underwater non-dispersible concrete
CN115745518A